Effect of Initial Cooling of Fruit and Vegetable Products on Storage - To‘rakeldiyev Javlonbek Ravshanbek o‘g‘li (Web of Journals Publishing, 2023)
One of the most effective technological measures to reduce losses in storage of fruits and vegetables is their initial cooling. One of the most effective technological measures to reduce losses in storage of fruits and vegetables is their initial cooling. The essence of this method is to immediately cool the fruits and vegetables to the optimum temperature for transportation and storage after harvesting.
Keywords: storage, fruit and vegetable products, agro-industrial complex, storage losses, product quality.